PENGEMBANGAN MODEL INTUITION BASED LEARNING (IBL) DENGAN SCIENTIFIC APPROACH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI SMA NEGERI 2 SRAGEN - Nok Yeni Heryaningsih; Riyadi Riyadi; Budi Usodo (Jurnal Pembelajaran Matematika, 2015)
Abstract: The aim of the research was to produce Intuition Based Learning (IBL) model and supporting learning with Scientific Approach in solving problems to increase mathematics students’ achievement that valid, practical and effective. The type of the research was a Research and Development (R&D). The subjects of the research were grade XI MS 6 and XI MS 4 students of SMAN 2 Sragen, Central Java on Academic year 2014/2015. IBL model development process was adopt from Plomp and Borg & Gall development model. They were (1) Collect the informations and studying of theories in Preliminary Investigations Phase, (2) Design of IBL model and supporting learning material (Lesson Plan, Worksheet, Problem sheet, and learning paper) and then design research instruments, (3) Realize the IBL model and supporting learning material that was design to be First Draft, (4) Do validation of the first draft, testing the IBL model in the classroom, and then do revisions, (5) Conduct Focus Group Discussion (FGD) to evaluate the result of IBL model testing in the classroom, then will be revised to the next IBL model testing. The results of the reasearch were produce IBL model and supporting learning material (Lesson Plan, Worksheet, Problem sheet, and learning paper) with scientific approach in solving problems to increase mathematics students’ achievement that valid, practical and effective. These are steps of IBL model in the classroom, (1) Opening with apperception, motivations and build students’ positif perceptions, (2) Students divided into several groups, (3) Teacher explains the material generally, (4) Group discussion with 5M activity (based on Scientific approach), (5) Exercise to solve open ended problem individually with steps that could appear students’ intuition: Preparations, Inkubation, Ilumination and Verification, (6) Closure with review of students have learned or giving homework.Keywords: Development of model, Learning model, intuition, scientific approach, students’ achievement.